Pater’s Poikilia — auto-références, métaphores et impressions dans Platon et le platonisme (1893) - Jean-Baptiste Picy (Cahiers Victoriens et Edouardiens)
Walter Pater’s Plato and Platonism (1893) is too often considered as distinct or exempt from the author’s usual idiosyncrasies of style. Building on William Shuter’s 1997 challenge to this traditional view, the aim of this paper is to demonstrate Pater’s unchanged attitudes and assign a positive value to his difficult, puzzling but eventually coherent use of imagery and inter-textual self-reference. Deconstructing Plato’s supposed rejection of « Poikilia » (confusing variety of imitative reference), Pater is shown to go beyond the dialectic opposition of Plurality vs. Unity or Movement vs. Rest. Evidencing still active longings to fulfil the initial Heraclitean intentions set out in « Diaphaneitè » (1864), the last work to be published in his life-time thus reasserts its position in the continuum of Pater’s permanently interconnected writing and time-conscious quest for « dry light ».